2014
DOI: 10.1186/1745-9974-10-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid suppression therapy on gastroesophageal reflux and cough in idiopathic pulmonary fibrosis: an intervention study

Abstract: BackgroundChronic cough affects more than 70 percent of patients with Idiopathic Pulmonary Fibrosis and causes significant morbidity. Gastroesophageal reflux is the cause of some cases of chronic cough; and also has a postulated role in the aetiology of Idiopathic Pulmonary Fibrosis. A high prevalence of acid; and more recently non-acid, reflux has been observed in Idiopathic Pulmonary Fibrosis cohorts. Therefore, gastroesophageal reflux may be implicated in the pathogenesis of cough in Idiopathic Pulmonary Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 37 publications
0
41
1
3
Order By: Relevance
“…Moreover, the presence of acid in the distal oesophagus may induce cough, probably through an oesophageal-tracheobronchial reflex [47]. Disappointingly, a study by KILDUFF et al [48] showed no improvement of cough by anti-acid treatments, but a paradoxical increase in non-acid reflux. It might well be that non-acid reflux is influencing cough more than acidic reflux [48].…”
Section: Comorbidities Influencing Coughmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, the presence of acid in the distal oesophagus may induce cough, probably through an oesophageal-tracheobronchial reflex [47]. Disappointingly, a study by KILDUFF et al [48] showed no improvement of cough by anti-acid treatments, but a paradoxical increase in non-acid reflux. It might well be that non-acid reflux is influencing cough more than acidic reflux [48].…”
Section: Comorbidities Influencing Coughmentioning
confidence: 98%
“…Disappointingly, a study by KILDUFF et al [48] showed no improvement of cough by anti-acid treatments, but a paradoxical increase in non-acid reflux. It might well be that non-acid reflux is influencing cough more than acidic reflux [48]. Unfortunately, cough itself may also increase trans-diaphragmatic pressure and promote GORD [47].…”
Section: Comorbidities Influencing Coughmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, more than 50% of patients with interstitial lung disease could have cough caused by other causes such as asthma, rhinitis or gastro-oesophageal reflux [18,19]. However, IIP may directly cause cough as inflammation is not limited to the parenchyma, and disrupted airway epithelium [20] with inflammatory mediators known to provoke cough having been detected in such patients [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Gastro-oesophageal reflux disease (GORD) has been suggested as a potential contributor to the pathophysiology of IPF and cough (40). However, in one study the use of acid-suppressing medication did not improve cough and led to a paradoxical increase in non-acid reflux (41). Corticosteroids have been shown to improve cough in one small RCT and may be used at a tapering dose if beneficial (34).…”
Section: Coughmentioning
confidence: 99%